Middle East and North Africa Economic Monitor, October 2017 : Refugee Crisis in MENA, Meeting the Development Challenges - Devarajan, Shantayanan; Mottaghi, Lili (Washington, D.C.: World Bank, 2017)
The pickup in economic activity in the Middle East and North Africa (MENA) region is expected to continue in 2018 and 2019. MENA's oil exporters and oil importers both are benefitting from improved global growth; increased trade with trading partners in Europe and Asia; more stabilized commodity markets, especially oil; and some reforms undertaken in the region. The World Bank estimates that growth will accelerate to above 3 percent in 2019. Growth, however, remains below potential as crises and conflicts continue to damage output and reduce employment. While MENA has experienced more frequent conflicts than any other part of the world, by its magnitude, the refugee crisis represents something new. The protracted stay of refugees in hosting communities, now in its sixth year, not only has increased the risk to MENA's economic outlook but also has brought refugees' long-term development challenges to the forefront. Meeting these enormous challenges requires collective efforts.